Regulation of Glucose, Fatty Acid and Amino Acid Metabolism by Ubiquitination and SUMOylation for Cancer Progression - Zhu, Shunqin; Gu, Hongyu; Peng, Cheng; Xia, Fanwei; Cao, Huan; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitination and SUMOylation, which are posttranslational modifications, play prominent roles in regulating both protein expression and function in cells, as well as various cellular signal transduction pathways. Metabolic reprogramming often occurs in various diseases, especially cancer, which has become a new entry point for understanding cancer mechanisms and developing treatment methods. Ubiquitination or SUMOylation of protein substrates determines the fate of modified proteins. Through accurate and timely degradation and stabilization of the substrate, ubiquitination and SUMOylation widely control various crucial pathways and different proteins involved in cancer metabolic reprogramming. An understanding of the regulatory mechanisms of ubiquitination and SUMOylation of cell proteins may help us elucidate the molecular mechanism underlying cancer development and provide an important theory for new treatments. In this review, we summarize the processes of ubiquitination and SUMOylation and discuss how ubiquitination and SUMOylation affect cancer metabolism by regulating the key enzymes in the metabolic pathway, including glucose, lipid and amino acid metabolism, to finally reshape cancer metabolism.